The application of targeted nanopore sequencing for the identification of pathogens and resistance genes in lower respiratory tract infections - Zhang, Hongying; Wang, Meng; Han, Ximei; Wang, Ting; Lei, Yanjuan; Rao, Yu; Xu, Peisong; Wang, Yunfei; Gu, Hongcang (Frontiers in Microbiology, 2022)
Lower respiratory tract infections (LRTIs) are one of the causes of mortality among infectious diseases. Microbial cultures commonly used in clinical practice are time-consuming, have poor sensitivity to unculturable and polymicrobial patterns, and are inadequate to guide timely and accurate antibiotic therapy. We investigated the feasibility of targeted-nanopore sequencing (TNPseq) for identification of the pathogen and antimicrobial resistance (AMR) genes across suspected LRTIs patients. TNPseq is a novel approach, which was improved based on nanopore sequencing to identification of bacterial and fungal infections of clinical relevance. This prospective study recruited 146 suspected LRTIs patients with median age 61 years. The potential pathogens from these patients were detected by both TNPseq and the traditional culture workups. We compared the performance between two methods among 146 LRTIs-related specimens. AMR genes were also detected by TNPseq to prompt the proper utilization of antibiotics. At least one pathogen was detected in 133 (91.1%) samples by TNPseq, but only 37 (25.3%) samples occurred positive isolates by culture among 146 specimens. TNPseq possessed higher sensitivity than the conventional culture method (91.1% vs. 25.3%, P<0.001) in identifying pathogens. It detected more samples with bacterial infections (P<0.001) and mixed infections (P<0.001) compared to the clinical culture tests. The most frequent AMR gene identified by TNPseq was blaTEM (n=29), followed by blaSHV (n=4), blaKPC (n=2), blaCTX-M (n=2), and mecA (n=2). Furthermore, TNPseq discovered five possible multi-drugs resistance specimens. TNPseq is efficient to identify the pathogens early, thus assisting physicians to conduct the timely and precise treatment for patients with suspicion LRTIs.